THE INFLUENCE OF THE ETHYLMETHYLHYDROXYPYRINE MALATE ON THE ABSOLUTE QUANTITY OF ERYTHROCYTE ISLETS IN THE CONDITION OF SULFUR DIOXIDES IMPACT ON THE DIFFERENT STAGES OF ONTOGENY - O. A. Ovsyannikova; D. V. Karpeeva; M. D. Osipenko (SINAPS LLC, 2017)
Anthropogenic impact leads not only to contamination of environmental components, but also to the negative impact on the human body, especially blood is very sensitive to the effects of unfavorable environmental factors. Therefore, the goal of the work is to study the influence of the ethylmethylhydroxypyrine malate on the absolute quantity of erythrocyte islets in the condition of sulfur dioxides impact on the different stages of ontogeny. 90 white mongrel male rats were used as materials and methods in the study, from which 3 groups of species were formed. Rats of different ages were examined for the experiment. For 5 days they were kept in a hermetically closed seeding chamber for the same period of time and under the same conditions as the experimental ones, but without the presence of a sulfur-containing gas. Natural industrial sulfur-containing gas was applied as the toxic agent of the Astrakhan gas-condensate field. According to the studies, it was found that the use of the ethylmethylhydroxypyrine malate against the background of intoxication gaseous sulfur pollutants leads to a relativenormalization of the proliferation and maturation of erythrocytes at all stages of the studied ontogeny. This allows us to consider this preparation as an effective means of neutralizing the negative effects of this toxicants influence. Also it was found that the young animals have a positive effect of the ethylmethylhydroxypyrine malate, and the old animals do not show a statistically significant effect. Therefore, the presented results indicate the possibility of increasing the body's resistance to chemical components of gas with the help of antihypoxic and antioxidant action of the ethylmethylhydroxypyrine malate